Discovery of a first-in-class inhibitor of sulfide:quinone oxidoreductase that protects against adverse cardiac remodelling and heart failure. Issue 7 (16th June 2021) - Jackson, Michael R; Cox, Kristie D; Baugh, Simon D P; Wakeen, Luke; Rashad, Adel A; Lam, Patrick Y S; Polyak, Boris; Jorns, Marilyn Schuman
Abstract: Aims: Hydrogen sulfide (H2 S) is a potent signalling molecule that activates diverse cardioprotective pathways by post-translational modification (persulfidation) of cysteine residues in upstream protein targets. Heart failure patients with reduced ejection fraction (HFrEF) exhibit low levels of H2 S. Sulfide:quinone oxidoreductase (SQOR) catalyses the first irreversible step in the metabolism of H2 S and plays a key role in regulating H2 S-mediated signalling. Here, the aim of this study was to discover a first-in-class inhibitor of human SQOR and evaluate its cardioprotective effect in an animal model of HFrEF. Methods and results: We identified a potent inhibitor of human SQOR (STI1, IC50 = 29 nM) by high-throughput screening of a small-molecule library, followed by focused medicinal chemistry optimization and structure-based design. STI1 is a competitive inhibitor that binds with high selectivity to the coenzyme Q-binding pocket in SQOR. STI1 exhibited very low cytotoxicity and attenuated the hypertrophic response of neonatal rat ventricular cardiomyocytes and H9c2 cells induced by neurohormonal stressors. A mouse HFrEF model was produced by transverse aortic constriction (TAC). Treatment of TAC mice with STI1 mitigated the development of cardiomegaly, pulmonary congestion, dilatation of the left ventricle, and cardiac fibrosis and decreased the pressure gradient across the aortic constriction. Moreover, STI1 dramatically improved survival, preserved cardiac function, and prevented the progression to HFrEF by impeding the transition from compensated to decompensated left ventricle hypertrophy. Conclusion: We demonstrate that the coenzyme Q-binding pocket in human SQOR is a druggable target and establish proof of concept for the potential of SQOR inhibitors to provide a novel therapeutic approach for the treatment of HFrEF. Graphical Abstract: